PENGARUH UKURAN PERUSAHAAN, RASIO HUTANG PADA MODAL, MARGIN LABA KOTOR DAN BIAYA OPERASIONAL TERHADAP BEBAN PAJAK PENGHASILAN BADAN - Mega Triana; Andar Febyansyah (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This research was conducted to analyze The Effect of Firm Size, Debt to Equity Ratio, Gross Profit Margin, and Operational Cost on Corporate Income Tax Burden either partially or simultaneously. The sampling method is purposive sampling. The number of samples used in this study were 10 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) with a total sample of 50 data. The type of data is secondary data sourced from the Indonesia Stock Exchange. The data analysis method used is multiple linear regression analysis. The findings of this study are based on the results of the t-test, it can be concluded that partially there is a negative influence between the ratio of DER to corporate income tax expenses and for operating costs, it partially has a positive effect on the burden of corporate income tax on pharmaceutical companies listed on the Stock Exchange for the 2016-2020. Partially, company size and gross profit margin have no effect on the burden of corporate income tax on pharmaceutical companies listed on the IDX for the 2016-2020. Based on the results of the F test, it is concluded that company size, DER, GPM and operating costs have a positive effect on corporate income tax expenses in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2016-2020.